Aislamiento Y Caracterización De Metabolitos Secundarios Mayoritarios Del Fruto De Annona Montana - Valdivieso Flores, Mónica Cecibel (2012)
In the present investigation the isolation of six was realized metabolitos secondary, from the fruit Annona Montana. The isolated compounds presented Rf of: a) 0.1, b) 0.2, c) 0.4, d) 0.6, e) 0.7, f) 0.9; fusion point: a) 280-290 °C, b) 109-130 °C, c) 310-320 °C, d) 194-200 °C, e) 248-253 °C, f) 235-240 °C. Of three extracts obtained with the solvents: hexane, ethyl acetate and methanol, selected the most cytotoxic previous evaluation of his activity in lines of human cancer, information considered from the results obtained in the Center of Cellular and Molecular Biology in the area of toxicological Genetics of Universidad Técnica Particular de Loja. The isolation realized it from the methanolic extract of the fruit, in view of his polar characteristic and to his considerable cytotoxic percentage opposite to lines of human cancer, in contrast, the extract hexane and ethyl acetate, they presented minor level of citotóxicidad. The division effected by means of column chromatography (CC) with the help of chromatography in thin cap (CCF) for the check of praise compounds isolated for it ascending polaridad used organic solvents; and as developers Sulfate Cérico and ultraviolet light (lamp UV of 254 and 366 nm). The purification of the majority compounds was realized from 320 resultant fractions of the division in chromatography in column of which there were obtained six fractions joined according to related characteristics and Rf exposed in chromatography of thin cap (CCF). The obtained results allow to know and to characterize compounds that constitute the medicinal plants with important traditional application as source of natural raw material.